Design of switchable band‐notched frequency selective absorber. Issue 10 (2nd July 2019) - Guo, Min; Chen, Qiang; Zheng, Yuejun; Sang, Di; Fu, Yunqi
Abstract: An active band‐notched frequency selective absorber (BNFSA) with switchable notch band is proposed in this article. The BNFSA is a two‐layer structure composed of a lossy layer at the top and a ground plane at the bottom, separated by an air spacer. The element of the lossy layer is a lumped‐resistor‐loaded metallic dipole with a parallel LC resonance structure, which is realized by complementary n‐shaped resonator (CnR) inserted in the center, and PIN diode is welded at two arms of CnR. The bias circuit printed on the back of the substrate of the lossy layer connects to anode and cathode of the diode by via hole and isolates by the inductor. Simulation results show that the notch bands are located at 4.50 and 6.81 GHz when the diode sets to ON and OFF, respectively. To validate the performance of switchable BNFSA, the prototypes are fabricated and measured, reasonable agreement between simulated and measured results is obtained.